Pedagogy of Legal Education in India: Contemporary Perspective - Shamota, Rahul; Goyal, Shreya (Trinity Law Review, 2023)
Every discipline has its own terminologies that are alien to outsiders. Legal discipline is no different and the terminology of law is so complex that it is impossible for a layman to understand the same even sometimes the legal jurist finds it difficult to make the layman understand the same. Legal education is similar to science that delivers the students the knowledge of principles and provisions of legal system that they are able to employ in their respective future. Legal education is often overlooked from the perspective of socio-legal, historical, economic and political perspectives and is one of the most complex multidisciplinary science. There is a serious need to look for the development and changes that need to be made in the old age pedagogy in legal education after witnessing the changes in contemporary structure in India. The changes that are required to be made are not only to make legal education in India more purposeful but also the need for changes to be adopted to keep up with the pace of the changing world. The changes needed to be made not only focused to make the students understand the terminology of the complexity of legal education but also to make them capable to have the ability to reason beyond the four walls of the court.
Keywords: Legal Education; Research; Legal Language; Pedagogy